2015
DOI: 10.18632/oncotarget.5201
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of the TL1A/DR3 axis in chronic lymphocytic leukemia

Abstract: TNF-like ligand 1A (TL1A) and its unique receptor death receptor 3 (DR3) acts as broad T-cell costimulator involved in regulatory mechanisms of adaptive immune response under physiological and pathological settings. Moreover, we have recently shown that TL1A negatively regulates B-cell proliferation. Despite increasing interest on the TL1A/DR3-axis functions, very little is known on its expression and role in leukemia. In this study, we investigated the expression and function of TL1A/DR3 axis in chronic lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…Our lab extended these findings and showed that in the absence of cIAPs DR3 stimulation allowed full‐blown apoptosis induction in the leukemia cell lines TF‐1 and Ku812F . Notably, DR3 expression has also been reported in B cells isolated from patients with chronic lymphocytic leukemia . Combinatorial treatments with SMAC mimetics and DR3 agonists could therefore hold therapeutic potential in some cancer entities.…”
Section: Molecular Mechanisms Of Dr3 Signalingsupporting
confidence: 58%
See 1 more Smart Citation
“…Our lab extended these findings and showed that in the absence of cIAPs DR3 stimulation allowed full‐blown apoptosis induction in the leukemia cell lines TF‐1 and Ku812F . Notably, DR3 expression has also been reported in B cells isolated from patients with chronic lymphocytic leukemia . Combinatorial treatments with SMAC mimetics and DR3 agonists could therefore hold therapeutic potential in some cancer entities.…”
Section: Molecular Mechanisms Of Dr3 Signalingsupporting
confidence: 58%
“…Notably, DR3 expression has also been reported in B cells isolated from patients with chronic lymphocytic leukemia [39]. Combinatorial treatments with SMAC mimetics and DR3 agonists could therefore hold therapeutic potential in some cancer entities.…”
Section: Cell Death Pathways Triggered By Dr3mentioning
confidence: 98%
“…The receptor stimulates sNF-kappa B activity and regulates cell apoptosis. TNFRSF25 was differentially expressed activating CLL cells and predominantly detecting in those with early clinical stage disease (37), and probably alters the balance between cell proliferation and death, in uencing CLL physiopathology and results in the clinic.…”
Section: Disscusionmentioning
confidence: 99%
“…TNF-like ligand 1A (TL1A; also known as TNFSF15 or VEGI), is a unique cytokine produced by endothelial cells, T cells, macrophages, monocytes and dendritic cells, which inhibits proliferation and angiogenesis of endothelial cells 5,67.…”
Section: Introductionmentioning
confidence: 99%